Soybean: Evaluation of Inoculation - T. M. Albuquerque; O. Ortez; G. I. Carmona; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2017)
Most of the nitrogen (N) required by a soybean plant is supplied via biological nitrogen fixation (BNF). When BNF is adequately established in the soil, soybean can obtain up to 50 to 75% of its N from the air. This project aims to quantify the response to inoculation for soybean in its second year in a field without previous history of this crop. Due to this objective, a field study was conducted during the 2015 and 2016 growing seasons at Ottawa, KS (East Central experiment field location). The treatments consisted of five different N-management approaches: non-inoculated (NI), inoculated ×1 (I×1), inoculated ×2 (I×2), inoculated ×3 (I×3), and non-inoculated but fertilized with 300 lb N/a (NF) as the main N source. In 2015, yields among treatments did not differ significantly from one another. In 2016, yields ranged from 36 to 59 bushels per acre. Greater yields were recorded when fertilized with 300 lb N/a, while lowest yield was related to the non-inoculated scenario. Treatments presented significant yield difference; however, the scenario with 300 lb N/a did not differ from the inoculated ×3; while the inoculated treatments were not different for the yield factor. In summary, further research should be pursued to be more conclusive as to the best management approach for N in soybeans in an area without history of this crop.
Keywords: inoculation; soybean; nitrogen; N fertilizer; yields